EFEKTIFITAS METODE PEMBELAJARAN TOTAL PHYSICAL RESPONSE (TPR) DALAM MENINGKATKAN PENGUASAAN KOSAKATA BAHASA INGGRIS BAGI SISWA TUNANETRA KELAS VII DI SLB A KOTA PAYAKUMBUH - Aulia Rahman (Universitas Negeri Padang, 2014)
Abstrak The background of this research is found by the writer ini class VII Junior High School SLB A Kota Payakumbuh. Where the student not able to speech English because the English vocabulary authority than to less. On the research, researcher used pre experimental design with kind one group pretest – posttest design, where the subject of research does a pretest before give a treatment and posttest after give a treatment with a Total Physical Response method. Furthermore the value of the activity pre-test and post-test were processed and compared by Mann Whitney U test. Results of this study indicate that the Total Physical Response method has improve the english vocabulary authority for blind student in class VII SLB A Kota Payakumbuh. Kata Kunci: Siswa Tunanetra; Penguasaan Kosakata; Metode Total Physical Response